The microbiome of the skin - Adamczyk, Katarzyna; Garncarczyk, Agnieszka A.; Antończak, Paweł P. (Przegląd dermatologiczny, 2018)
Skin is the most external organ of the body, protecting it from environmental factors. The barrier functions of the skin are significantly supported by the cutaneous microbiome (bacteria, fungi, mites and viruses). To perform its functions, the microbiome must have a certain size and diversity. The microbiome balance can be disrupted by internal and environmental factors. Disturbed homoeostasis is observed, among other conditions, in the course of atopic dermatitis, psoriasis, acne vulgaris, rosacea, and seborrhoeic dermatitis. The skin is inhabited primarily by four phyla of bacteria: Actinobacteria, Firmicutes, Bacteroidetes and Proteobacteria. The dominant fungal and mite species residing on the skin are lipophilic fungi of the genus Malassezia and Demodex, respectively. Viruses are an unstable but essential element of the skin microbiome, particularly viruses containing double stranded DNA (dsDNA) such as Polyomaviridae and Papillomaviridae.